Framework-supported solid waste-based cementing material and preparation method thereof
Through simple ball milling and addition of exciters and ion complexing agents, the gelling activity of cinder and iron tailings is stimulated, and the skeleton-supported solid waste-based gelling material is formed, which solves the problems of high energy consumption and low iron tailings in the prior art, and realizes the preparation of high-performance gelling materials and the high-value utilization of solid waste.
Patent Information
- Application Number
- CN202411835660.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
When the prior art stimulates the gelling activity of cinder and iron tailings, it requires complex ball milling, chemical activation and heat treatment processes, which have high energy consumption and depend on strong alkali or strong acids, and the iron tailings dosage is low, so it is unable to effectively utilize the combination of cinder-iron tailings-desulfurization ash.
A simple ball milling process is adopted and a small amount of exciter and ion complexing agent is added. Through calcification, complexation-chelation and hydration reaction, the reaction activity of cinder and iron tailings is improved to form a skeleton-supported solid waste-based gelling material.
The prepared skeleton-supported solid waste-based gelling material has excellent performance and its mechanical properties reach the level of 42.5R silicate cement, reducing dependence on strong alkalis or strong acids, simple process and achieving high-value utilization of solid waste.
Smart Images

Figure BDA0005186635160000051 
Figure BDA0005186635160000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a skeleton-supported solid waste-based cementitious material and a preparation method thereof. Background Art
[0002] Under the background of "double carbon", the building materials industry is under great pressure to reduce carbon emissions. Cement has the advantages of high strength, durability and good workability, and is an indispensable cementitious material in the building materials industry. However, the preparation process of cement has high energy consumption and high carbon emissions, which seriously limits the carbon emission reduction process of the building materials industry. Therefore, it is urgent to find more environmentally friendly cementitious materials to partially or completely replace cement. Solid waste-based cementitious materials are a new type of cementitious materials produced by the synergistic effect between solid wastes. They can replace cement in specific fields and are conducive to promoting carbon emission reduction in the building materials industry.
[0003] Coal slag is the tailings produced after coal combustion. Like fly ash, they are both byproducts of coal combustion. The two have similar chemical compositions and high silicon and aluminum contents. They are potential components for preparing cementitious materials. However, the chemical activity of coal slag is much lower than that of fly ash under normal conditions, resulting in a much lower utilization rate of coal slag than that of fly ash. Desulfurization ash is produced during dry or semi-dry flue gas desulfurization, and contains components such as CaSO3·0.5H2O, CaSO4·0.5H2O, CaSO4·2H2O and Ca(OH)2. The sulfate and calcium hydroxide components contained in the desulfurization ash make it possible to use it as an activator, but its complex composition and poor stability restrict its application development. Iron tailings are solid wastes produced after ore dressing. Currently, only about 7% of iron tailings are recycled and reused, and the rest are stored in the form of tailings ponds, which pollutes the environment and poses safety hazards. The chemical composition of iron tailings is similar to that of cementitious materials, containing a large amount of SiO2 and Al2O3, but its reaction activity is low and it needs to be treated before being used as a cementitious material.
[0004] At present, scholars at home and abroad have conducted research on the preparation of cementitious materials from coal slag, desulfurized ash and iron tailings. In order to stimulate the gelling activity of coal slag and iron tailings powder, mechanical grinding, chemical stimulation and heat treatment and their combination are often used. Patent CN113620618A mixes the powder obtained by mixing granite powder and coal slag with sodium hydroxide, calcium oxide, sodium carbonate and / or sodium bicarbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide and sodium silicate, and then roasts it at 450-650℃ for 1-3h to obtain a cementitious material containing coal slag components. Patent CN114988735A first mixes a mixture of calcium oxide and trisodium phosphate with granite powder and coal slag by ball milling, and then mixes the obtained powder with water glass and water to obtain a phosphate-based polymer cementitious material. Patent CN117069396A uses solid wastes such as iron tailings, desulfurization ash, slag and fly ash as raw materials, and prepares a cementitious material with a strength higher than that of traditional silicate cement after screening and staged grinding, wherein the iron tailings content is 5%-15%. Patent CN117466589A uses soluble sodium salt, KH-550, sodium castor oil sulfonate, triisopropanolamine and sodium tetradecyl sulfate to pre-treat the iron tailings, improves the surface electronegativity of the iron tailings, and improves the compactness of the iron tailings pavement base material. Patent CN117209176A uses dry desulfurization ash as an activator to activate slag, steel slag, fly ash, cement, and volcanic ash to prepare solid waste cementitious materials. In the preparation process, the desulfurization ash first needs to be treated with water and dried, and at the same time mixed with desulfurized gypsum, phosphogypsum, titanium gypsum, sodium sulfate, soda ash, water glass, and bauxite as an activator of the material. The article "Preparation and Performance Study of Iron Tailings Powder-Desulfurization Ash Cementitious Materials" by Chen Xing et al. uses ball-milled activated iron tailings powder, desulfurization ash, and slag powder as raw materials, and uses sodium hydroxide and calcium sulfate as composite activators to prepare iron tailings powder-desulfurization ash cementitious materials. The optimal dosage of iron tailings powder is 20%.
[0005] The above studies have proved that cementitious materials can be prepared from coal slag, desulfurized ash or iron tailings, but there are still some problems: (1) In order to effectively stimulate the gelling activity of coal slag and iron tailings, a combination of ball milling, chemical activation and thermal activation is required. A large amount of alkaline reagent is used as an activator in the activation process, and the activation process is complex and energy-intensive. (2) In addition to SiO2 and Al2O3, coal slag and iron tailings also have a high iron content. In addition to the high crystallinity of the silicon and aluminum components, the high content of iron-containing components is another major reason for the low gelling activity of coal slag and iron tailings. However, current research mainly focuses on releasing and improving the activity of silicon and aluminum components in coal slag and iron tailings, and lacks research on stimulating iron-containing components. (3) At present, the amount of iron tailings added when preparing composite cementitious materials using iron tailings is low, and there is no research on the simultaneous use of coal slag-iron tailings-desulfurized ash to prepare cementitious materials. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a skeleton-supported solid waste-based cementitious material and a preparation method in view of the shortcomings of the prior art. The preparation method uses coal slag, desulfurization ash and iron tailings as raw materials, and through simple ball milling and adding a small amount of activator and ion complexing agent, the prepared skeleton-supported solid waste-based cementitious material has excellent performance and the mechanical properties reach the level of 42.5R silicate cement.
[0007] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0008] A skeleton-supported solid waste-based cementitious material, whose raw materials include: coal slag, desulfurization ash, iron tailings, ion complexing agent, activator and water; wherein the main raw materials include coal slag, desulfurization ash and iron tailings, which are calculated by weight as follows: 30-45 parts of coal slag, 5-10 parts of desulfurization ash and 50-60 parts of iron tailings; ion complexing agent, activator and water are calculated as additives, wherein the ion complexing agent accounts for 0.05%-0.2% of the main raw materials, the activator accounts for 2%-6% of the main raw materials, and water accounts for 30%-50% of the main raw materials.
[0009] In the above scheme, the ion complexing agent is a mixture of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate; wherein the mass ratio of the triethanolamine, the triisopropanolamine and the disodium ethylenediaminetetraacetate is (35-50):(40-60):(5-10).
[0010] In the above scheme, the activator is a mixture of sodium citrate and sodium hydroxide; wherein the mass ratio of the sodium citrate to the sodium hydroxide is (50-60): (40-50).
[0011] In the above scheme, the coal slag is the tailings produced after the combustion of coal in a thermal power plant, and the maximum particle size is not greater than 2.35 mm; the total content of SiO2 and Al2O3 in the coal slag is greater than 70%, and the content of Fe2O3 is greater than 5%.
[0012] In the above scheme, the desulfurization ash is waste residue produced in the semi-dry flue gas desulfurization process of the steel plant, and the maximum particle size is not more than 5 μm; the SO3 content in the desulfurization ash is greater than 7%, and the CaSO3·0.5H2O content is greater than 35%.
[0013] In the above scheme, the maximum particle size of the iron tailings is not greater than 1 mm; the total content of SiO2 and Al2O3 in the iron tailings is greater than 30%, the CaO content is less than 35%, and the Fe2O3 content is greater than 10%.
[0014] The present invention also provides a method for preparing the above-mentioned skeleton-supported solid waste-based gelling material, comprising the following steps:
[0015] (1) pre-treating coal slag, desulfurization ash, and iron tailings; then mixing the pre-treated coal slag, desulfurization ash, iron tailings, and an ion complexing agent according to a ratio and subjecting them to ball milling to obtain a mixture;
[0016] (2) uniformly mixing the obtained mixture with an activator and water to obtain a cementitious material slurry;
[0017] (3) injecting the obtained cementitious material slurry into a mold for molding and curing, and obtaining the skeleton-supported solid waste-based cementitious material after solidification.
[0018] In the above scheme, the pretreatment in step 1 is specifically: drying the coal slag at 100-110°C, keeping the desulfurized ash at 50-70°C for 0.5-2h, and drying the iron tailings at 100-110°C; the ball milling time is 1-3h.
[0019] In the above scheme, the specific surface area of the mixture in step 1 is 450-550m 2 / Kg.
[0020] In the above scheme, the curing process in step 3 is to first keep the molded cementitious material slurry in a mold at a temperature of 40-60° C. for 1-2 days, and then demold the molded test piece and place it at room temperature for curing.
[0021] In the present invention, the skeleton-supported gelling material undergoes the following reactions during preparation and curing:
[0022] (1) Ball milling: During ball milling, the particle size of the material is reduced under the action of external forces such as friction and shear force, increasing the specific surface area. At the same time, the silicon-oxygen / aluminum bonds in the coal slag and iron tailings are destroyed, producing active silicon-aluminum components and improving the reaction activity of the material.
[0023] (2) Calcification: During the ball milling process, calcium ions in the CaSO3·0.5H2O, CaSO4·0.5H2O, and CaSO4·2H2O components contained in the desulfurization ash are adsorbed on the surface of the coal slag and iron tailings particles, affecting the chemical environment of the silicon and aluminum elements in the alkaline environment provided by Ca(OH)2. The solubility of silicon and aluminum minerals is increased through calcification, and easily soluble calcium aluminum silicates are generated, providing more reactants for the hydration reaction.
[0024] (3) Complexation-chelation: On the one hand, the ionic complexing agent reacts with SO3 in the desulfurized ash. 2- and SO4 2-The combined effect promotes the decomposition of the iron-containing phase in coal slag and iron tailings. On the other hand, the complexation promotes the continuous disordered migration of dissolved Fe, Al, Si and Ca ions in the liquid phase, avoiding the accumulation of ions and hydration products on the surface of coal slag and iron tailings, and promoting the random growth of hydration products in different positions. The disodium ethylenediaminetetraacetic acid in the complexing agent chelates with iron ions to reduce the concentration of iron ions in the solution, further improving the dissolution of the iron-containing phase in coal slag and iron tailings.
[0025] (4) Comprehensive hydration: ① Generation of C-SH: Under the combined action of Ca(OH)2 contained in the desulfurized ash and sodium hydroxide in the activator, the calcium aluminum silicate generated by calcification dissolves to release active silicon aluminum ions and generates CSH sol through hydration reaction. At the same time, sodium citrate in the activator can further promote the dissolution of coal ash and the precipitation of hydration products. ② Generation of iron silicon hydrogarnet: SO3 2- and SO4 2- It reacts with iron ions, aluminum ions and calcium ions to form plate-like iron silicate hydration products C2(F,A)3S3H2 and FeSO4·7H2O, in which the ion complexing agent acts as a carrier to transfer iron ions from coal slag and iron tailings to the hydration products. ③ Formation of C-FSH: The complexed iron formed under the action of the ion complexing agent replaces some silicon-oxygen tetrahedrons in the CSH gel to form CFSH gel.
[0026] (5) Skeleton support: Since the hardness of iron tailings is much higher than that of coal slag, the degree of destruction of iron tailings particles is much lower than that of coal slag under the same ball milling time, which enhances the reactivity of the surface layer of iron tailings, but the interior remains inert. During the hydration reaction, the active surface layer of the iron tailings participates in the hydration reaction, and the other substances of the iron tailings particles are closely combined through chemical reactions. At the same time, the relatively complete particle structures of the iron tailings overlap each other, forming a relatively complete "skeleton" inside the cementitious material, which supports the strength of the cementitious material. This is the main reason why the present invention can significantly increase the amount of iron tailings used.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The preparation method provided by the present invention uses coal slag, desulfurization ash and iron tailings as raw materials, and through simple ball milling and adding a small amount of activator and ion complexing agent, a skeleton-supported solid waste-based cementitious material with excellent performance is prepared under the joint action of active silicon and aluminum dissolution, iron-based hydration product compaction enhancement and particle skeleton support, thereby reducing the dependence of solid waste-based cementitious materials on strong alkali or strong acid during the active activation process; by optimizing the action mode of iron tailings, the skeleton support role of iron tailings in the strength development process of cementitious materials is highlighted, and the dosage of iron tailings in cementitious materials is significantly increased.
[0029] (2) In the preparation method provided by the present invention, under the joint action of desulfurized ash and ion complexing agent, the dissolution rate of silicon and aluminum in coal slag and iron tailings is improved through calcification and complexing-chelation, and the hydration reaction activity of the surface layer of coal slag and iron tailings is enhanced; the utilization rate of iron ions in coal slag and iron tailings is improved, and the iron ions are prompted to participate in the hydration reaction through complexing, and on the basis of generating CSH gel, plate-like iron-silicon hydrogarnet hydration products C2(F,A)3S3H2, FeSO4·7H2O and CFSH gel are further formed, thereby compacting the microstructure of the cementitious material and improving the performance of the cementitious material.
[0030] (3) The preparation method provided by the present invention has a simple process and realizes the high-value and large-scale utilization of coal slag, desulfurization ash and iron tailings solid waste. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0032] In a specific implementation manner, the coal slag used is the tailings produced after coal combustion in a thermal power plant, with a maximum particle size of no more than 2.35 mm; the desulfurization ash used is the waste slag produced in the semi-dry flue gas desulfurization process of a steel plant, with a maximum particle size of no more than 5 μm; the maximum particle size of the iron tailings used is no more than 1 mm; the chemical compositions of the three are shown in Table 1, and the CaSO3·0.5H2O content in the desulfurization ash is 41%.
[0033] Table 1 Chemical composition of materials
[0034]
[0035] Example 1
[0036] A method for preparing a skeleton-supported solid waste-based cementitious material comprises the following steps:
[0037] (1) The coal slag was dried at 105°C, the desulfurized ash was kept at 60°C for 1 hour, and the iron tailings were dried at 105°C; then 30 parts of the pretreated coal slag, 10 parts of desulfurized ash, 60 parts of iron tailings, and 0.2 parts of an ion complexing agent (0.2% of the total amount of coal slag, desulfurized ash, and iron tailings) were mixed and ball-milled for 2 hours to obtain a mixture with a specific surface area of 480 m 2 / Kg; wherein the ion complexing agent is a mixture of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate, and the mass ratio of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate is 35:60:5;
[0038] (2) The obtained mixture is mixed with 3 parts of an activator and 30 parts of water to obtain a cementitious material slurry; wherein the activator is a mixture of sodium citrate and sodium hydroxide, and the mass ratio of sodium citrate to sodium hydroxide is 50:50; the activator is 3% of the total amount of coal slag, desulfurization ash, and iron tailings; and the water is 30% of the total amount of coal slag, desulfurization ash, and iron tailings;
[0039] (3) injecting the obtained cementitious material slurry into a mold for molding and curing, and obtaining the skeleton-supported solid waste-based cementitious material after solidification; wherein the curing process is to first keep the molded cementitious material slurry in the mold at a temperature of 50°C for 2 days, and then demolding the molded test piece and placing it at room temperature for curing.
[0040] Example 2
[0041] A method for preparing a skeleton-supported solid waste-based cementitious material comprises the following steps:
[0042] (1) The coal slag was dried at 110°C, the desulfurized ash was kept at 60°C for 1 hour, and the iron tailings were dried at 110°C; then 45 parts of the pretreated coal slag, 5 parts of the desulfurized ash, 50 parts of the iron tailings, and 0.2 parts of the ion complexing agent (0.2% of the total amount of the coal slag, desulfurized ash, and iron tailings) were mixed according to the proportions and ball-milled for 2.5 hours to obtain a mixture with a specific surface area of 530 m 2 / Kg; wherein the ion complexing agent is a mixture of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate, and the mass ratio of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate is 35:60:5;
[0043] (2) The obtained mixture is mixed with 3 parts of an activator and 30 parts of water to obtain a cementitious material slurry; wherein the activator is a mixture of sodium citrate and sodium hydroxide, and the mass ratio of sodium citrate to sodium hydroxide is 50:50; the activator is 3% of the total amount of coal slag, desulfurization ash, and iron tailings; and the water is 30% of the total amount of coal slag, desulfurization ash, and iron tailings;
[0044] (3) injecting the obtained cementitious material slurry into a mold for molding and curing, and obtaining the skeleton-supported solid waste-based cementitious material after solidification; wherein the curing process is to first keep the molded cementitious material slurry in the mold at a temperature of 50°C for 2 days, and then demolding the molded test piece and placing it at room temperature for curing.
[0045] Example 3
[0046] A method for preparing a skeleton-supported solid waste-based cementitious material comprises the following steps:
[0047] (1) The coal slag was dried at 103°C, the desulfurized ash was kept at 60°C for 1 hour, and the iron tailings were dried at 103°C; then 40 parts of the pretreated coal slag, 8 parts of desulfurized ash, 52 parts of iron tailings, and 0.2 parts of an ion complexing agent (0.2% of the total amount of coal slag, desulfurized ash, and iron tailings) were mixed according to the proportions and ball-milled for 2.5 hours to obtain a mixture with a specific surface area of 550 m 2 / Kg; wherein the ion complexing agent is a mixture of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate, and the mass ratio of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate is 35:60:5;
[0048] (2) The obtained mixture is mixed with 3 parts of an activator and 30 parts of water to obtain a cementitious material slurry; wherein the activator is a mixture of sodium citrate and sodium hydroxide, and the mass ratio of sodium citrate to sodium hydroxide is 50:50; the activator is 3% of the total amount of coal slag, desulfurization ash, and iron tailings; and the water is 30% of the total amount of coal slag, desulfurization ash, and iron tailings;
[0049] (3) injecting the obtained cementitious material slurry into a mold for molding and curing, and obtaining the skeleton-supported solid waste-based cementitious material after solidification; wherein the curing process is to first keep the molded cementitious material slurry in the mold at a temperature of 50°C for 2 days, and then demolding the molded test piece and placing it at room temperature for curing.
[0050] Example 4
[0051] A method for preparing a skeleton-supported solid waste-based cementitious material comprises the following steps:
[0052] (1) The coal slag is dried at 105°C, the desulfurized ash is kept at 60°C for 1 hour, and the iron tailings are dried at 105°C; then 30 parts of the pretreated coal slag, 10 parts of the desulfurized ash, 60 parts of the iron tailings, and 0.1 parts of the ion complexing agent (0.1% of the total amount of the coal slag, desulfurized ash, and iron tailings) are mixed and ball-milled for 2 hours to obtain a mixture with a specific surface area of 500 m 2 / Kg; wherein the ion complexing agent is a mixture of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate, and the mass ratio of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate is 50:40:10;
[0053] (2) The obtained mixture is mixed with 3 parts of an activator and 30 parts of water to obtain a cementitious material slurry; wherein the activator is a mixture of sodium citrate and sodium hydroxide, and the mass ratio of sodium citrate to sodium hydroxide is 50:50; the activator is 3% of the total amount of coal slag, desulfurization ash, and iron tailings; and the water is 30% of the total amount of coal slag, desulfurization ash, and iron tailings;
[0054] (3) injecting the obtained cementitious material slurry into a mold for molding and curing, and obtaining the skeleton-supported solid waste-based cementitious material after solidification; wherein the curing process is to first keep the molded cementitious material slurry in the mold at a temperature of 50°C for 2 days, and then demolding the molded test piece and placing it at room temperature for curing.
[0055] Example 5
[0056] A method for preparing a skeleton-supported solid waste-based cementitious material comprises the following steps:
[0057] (1) The coal slag is dried at 107°C, the desulfurized ash is kept at 60°C for 1 hour, and the iron tailings are dried at 107°C; then 30 parts of the pretreated coal slag, 10 parts of the desulfurized ash, 60 parts of the iron tailings, and 0.05 parts of the ion complexing agent (0.05% of the total amount of the coal slag, desulfurized ash, and iron tailings) are mixed according to the proportions and ball-milled for 1.5 hours to obtain a mixture with a specific surface area of 500 m 2 / Kg; wherein the ion complexing agent is a mixture of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate, and the mass ratio of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate is 50:40:10;
[0058] (2) The obtained mixture is mixed with 4.5 parts of an activator and 40 parts of water to obtain a cementitious material slurry; wherein the activator is a mixture of sodium citrate and sodium hydroxide, and the mass ratio of sodium citrate to sodium hydroxide is 60:40; the activator is 4.5% of the total amount of coal slag, desulfurization ash, and iron tailings; and the water is 40% of the total amount of coal slag, desulfurization ash, and iron tailings;
[0059] (3) injecting the obtained cementitious material slurry into a mold for molding and curing, and obtaining the skeleton-supported solid waste-based cementitious material after solidification; wherein the curing process is to first keep the molded cementitious material slurry in the mold at 40°C for 1 day, and then demolding the molded test piece and placing it at room temperature for curing.
[0060] Example 6
[0061] A method for preparing a skeleton-supported solid waste-based cementitious material comprises the following steps:
[0062] (1) The coal slag was dried at 104°C, the desulfurized ash was kept at 60°C for 1 hour, and the iron tailings were dried at 104°C; then 40 parts of the pretreated coal slag, 8 parts of desulfurized ash, 52 parts of iron tailings, and 0.2 parts of an ion complexing agent (0.2% of the total amount of coal slag, desulfurized ash, and iron tailings) were mixed and ball-milled for 2 hours to obtain a mixture with a specific surface area of 530 m 2 / Kg; wherein the ion complexing agent is a mixture of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate, and the mass ratio of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate is 40:52:8;
[0063] (2) The obtained mixture is mixed with 6 parts of an activator and 50 parts of water to obtain a cementitious material slurry; wherein the activator is a mixture of sodium citrate and sodium hydroxide, and the mass ratio of sodium citrate to sodium hydroxide is 55:45; the activator is 6% of the total amount of coal slag, desulfurization ash, and iron tailings; and the water is 50% of the total amount of coal slag, desulfurization ash, and iron tailings;
[0064] (3) injecting the obtained cementitious material slurry into a mold for molding and curing, and obtaining the skeleton-supported solid waste-based cementitious material after solidification; wherein the curing process is to first keep the molded cementitious material slurry in the mold at a temperature of 55°C for 2 days, and then demolding the molded test piece and placing it at room temperature for curing.
[0065] Comparative Example 1
[0066] Comparative Example 1 is substantially the same as Example 1, except that no desulfurization ash is added during the ball milling of the mixture.
[0067] Comparative Example 2
[0068] Comparative Example 2 is substantially the same as Example 1, except that no ion complexing agent is added during the ball milling of the mixture.
[0069] Comparative Example 3
[0070] Comparative Example 3 is substantially the same as Example 1, except that no activator is added.
[0071] Comparative Example 4
[0072] Comparative Example 4 is substantially the same as Example 1, except that triethanolamine and triisopropanolamine are not added to the ion complexing agent.
[0073] Comparative Example 5
[0074] Comparative Example 5 is substantially the same as Example 1, except that: no disodium ethylenediaminetetraacetate is added to the ion complexing agent, and the mass ratio of triethanolamine to triisopropanolamine in the ion complexing agent is 35:60.
[0075] The compressive strength of the cementitious materials obtained in the above embodiments and comparative examples was tested at different ages using the test standard specified in GB 175 2023 General Portland Cement. The results are shown in Table 2.
[0076] Table 2 Cementitious material strength test results
[0077]
[0078] It can be seen from the test results in Table 1 that the skeleton-supported solid waste-based cementitious materials prepared in Examples 1-6 of the present invention have a 28d compressive strength exceeding 42.5 MPa, reaching the standard requirement of 42.5R grade general-purpose Portland cement.
[0079] Compared with Example 1, the compressive strength of the cementitious material prepared in Comparative Example 1 is lower than that of Example 1 at all ages. This is because the lack of the alkaline environment provided by the desulfurization ash weakens the calcification effect, resulting in a decrease in the dissolution rate of active silicon and aluminum components, which in turn causes the hydration process to slow down, the hydration products to decrease, and the material strength to decrease.
[0080] Compared with Example 1, the compressive strength of the cementitious material prepared in Comparative Example 2 at each age is lower than that of Example 1. This is because when the ion complexing agent is lacking in the components, it is impossible to effectively induce the dissolution of iron ions in the coal slag and iron tailings and the hydration reaction to generate C2(F,A)3S3H2, FeSO4·7H2O and CFSH hydration products, resulting in the strength of the material being provided only by the skeleton support of CSH and iron tailings, the density of the material microstructure decreases, and thus the strength of the material decreases.
[0081] Compared with Example 1, the compressive strength of the cementitious material prepared in Comparative Example 3 is lower than that in Example 1 at all ages. This is because the material components lack an activator. During the hydration reaction, the dissolution rate of active silicon and aluminum decreases, and the formation rate of CSH decreases, resulting in a decrease in the strength of the material. However, the strength of the material in Comparative Example 3 is higher than that in Comparative Example 1, which proves that the activation of desulfurization ash on coal slag and iron tailings plays an important role in the development of material strength.
[0082] Compared with Example 1, the compressive strength of the cementitious material prepared in Comparative Example 4 at each age is lower than that in Example 1. This is because when triethanolamine and triisopropanolamine are lacking in the ion complexing agent, the complexing effect is lost, the Fe, Al, Si and Ca ions dissolved in the solution cannot continue to migrate in the liquid phase, and the iron ions cannot participate in the hydration reaction in time, resulting in the inability to evenly disperse the hydration products in the material, and the yield of C2(F,A)3S3H2, FeSO4·7H2O and CFSH hydration products is reduced.
[0083] Compared with Example 1, the compressive strength of the cementitious material prepared in Comparative Example 5 is lower than that in Example 1 at all ages. This is because when the ion complexing agent lacks disodium ethylenediaminetetraacetic acid, the iron ions continuously released into the solution by the coal slag and iron tailings under the action of desulfurization ash and the complexing agent cannot undergo chelation, and the iron ion concentration in the solution cannot be effectively reduced, which limits the dissolution of iron ions in the coal slag and iron tailings, resulting in a decrease in iron-containing hydration products and a decrease in the density of the microstructure. However, the strength of the material in Comparative Example 5 is higher than that in Comparative Example 4, proving that in the ion complexing agent, the complexing effect that enables the effective migration of ions contributes more to the material strength than the chelating effect.
[0084] The above experimental results and comparative results prove that the skeleton-supported solid waste-based cementitious material prepared from coal slag, desulfurization ash and iron tailings of the present invention, in the presence of ion chelating agents and activators, induces the dissolution of iron ions in coal slag and iron tailings, and promotes the iron ions to participate in the hydration reaction through calcification and complexation-chelation, thereby forming various types of hydration products, compacting the internal structure of the material, and highlighting the skeleton supporting role of the iron tailings, thereby achieving an improvement in the mechanical properties of the material, and the mechanical properties of the material reach the level of 42.5R silicate cement.
[0085] In summary, the preparation method provided by the present invention uses coal slag, desulfurization ash and iron tailings as raw materials, and prepares a skeleton-supported solid waste-based cementitious material with excellent performance through simple ball milling and adding a small amount of activator and ion complexing agent.
[0086] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A skeleton-supported solid waste-based cementitious material, characterized in that: Its raw materials include: coal slag, desulfurization ash, iron tailings, ion complexing agent, activator and water; among them, the main raw materials include coal slag, desulfurization ash and iron tailings, which are calculated by weight as follows: 30-45 parts of coal slag, 5-10 parts of desulfurization ash and 50-60 parts of iron tailings; ion complexing agent, activator and water are calculated as additives, among which the ion complexing agent accounts for 0.05%-0.2% of the main raw materials, the activator accounts for 2%-6% of the main raw materials, and water accounts for 30%-50% of the main raw materials.
2. The skeleton-supported solid waste-based cementitious material according to claim 1, characterized in that: The ion complexing agent is a mixture of triethanolamine, triisopropanolamine and disodium ethylenediaminetetraacetate; wherein the mass ratio of the triethanolamine, the triisopropanolamine and the disodium ethylenediaminetetraacetate is (35-50):(40-60):(5-10).
3. The skeleton-supported solid waste-based cementitious material according to claim 1, characterized in that: The activator is a mixture of sodium citrate and sodium hydroxide; wherein the mass ratio of the sodium citrate to the sodium hydroxide is (50-60): (40-50).
4. The skeleton-supported solid waste-based cementitious material according to claim 1, characterized in that: The coal slag is tailings produced after coal combustion in a thermal power plant, and has a maximum particle size of no more than 2.35 mm; the total content of SiO2 and Al2O3 in the coal slag is greater than 70%, and the content of Fe2O3 is greater than 5%.
5. The skeleton-supported solid waste-based cementitious material according to claim 1, characterized in that: The desulfurized ash is waste residue produced in the semi-dry flue gas desulfurization process of a steel plant, and has a maximum particle size of no more than 5 μm; the SO3 content in the desulfurized ash is greater than 7%, and the CaSO3·0.5H2O content is greater than 35%.
6. The skeleton-supported solid waste-based cementitious material according to claim 1, characterized in that: The maximum particle size of the iron tailings is no more than 1 mm; the total content of SiO2 and Al2O3 in the iron tailings is greater than 30%, the CaO content is less than 35%, and the Fe2O3 content is greater than 10%.
7. The method for preparing a skeleton-supported solid waste-based cementitious material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) pre-treating coal slag, desulfurization ash, and iron tailings; then mixing the pre-treated coal slag, desulfurization ash, iron tailings, and an ion complexing agent according to a ratio and subjecting them to ball milling to obtain a mixture; (2) uniformly mixing the obtained mixture with an activator and water to obtain a cementitious material slurry; (3) injecting the obtained cementitious material slurry into a mold for molding and curing, and obtaining the skeleton-supported solid waste-based cementitious material after solidification.
8. The method for preparing a skeleton-supported solid waste-based cementitious material according to claim 7, characterized in that: The pretreatment in step 1 is specifically as follows: drying the coal slag at 100-110°C, keeping the desulfurized ash at 50-70°C for 0.5-2h, and drying the iron tailings at 100-110°C; the ball milling time is 1-3h.
9. The method for preparing a skeleton-supported solid waste-based cementitious material according to claim 7, characterized in that: The specific surface area of the mixture in step 1 is 450-550m 2 / Kg.
10. The method for preparing a skeleton-supported solid waste-based cementitious material according to claim 7, characterized in that: The curing process in step 3 is to first keep the molded cementitious material slurry in a mold at a temperature of 40-60° C. for 1-2 days, and then demold the molded test piece and place it at room temperature for curing.
Citation Information
Patent Citations
Method for preparing integrated cementing material by using granite stone powder and fire coal slag
CN113620618A
Method for preparing phosphoric acid-based geopolymer from low-activity solid waste
CN114988735A
Cementing material containing industrial solid waste, mine cemented filling material and preparation method of cementing material and mine cemented filling material
CN117069396A
Method for preparing solid waste cementing material by using dry desulfurization ash and solid waste cementing material
CN117209176A
Pavement base material of modified iron tailings as well as preparation and application methods of pavement base material
CN117466589A